Cross-border performance in European banking - Iftekhar Hasan; Ana Lozano-Vivas; Jesús Pastor (Bank of Finland, 2000)
Recent cross-country comparisons of bank efficiency have been based on pooled estimates of banks across countries and have typically assumed a common frontier and that differences in performance among banks are primarily due to disparities in certain country-specific aspects of banking technology.This paper argues that such comparisons of performance must take into account cross-country differences in economic conditions, demographics, and regulatory structures (environmental factors).Using a sample of banks from ten leading European countries, this paper provides detailed evaluations of the efficiency of banks in each country that operate both within and outside their own environments.The results indicate that adverse (advantageous) environmental conditions are a positive (negative) factor for the home banking industry and that technical efficiency is a significant deterrence to foreign competition.
URN:NBN:fi:bof-20140807206
Keywords: 330